2021
DOI: 10.1371/journal.pone.0250990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intestinal parasite infection on hematological profiles of pregnant women attending antenatal care at Debre Markos Referral Hospital, Northwest Ethiopia: Institution based prospective cohort study

Abstract: Background Intestinal parasitosis is a common disease that causes misery and disability in poor populations. The number of individuals affected is staggering. From two billion peoples who harbor parasites worldwide, 300 million suffer severe morbidity and more than 25% of pregnant women are infected with hookworm, which causes intestinal bleeding and blood loss, and has been most commonly associated with anemia. Intestinal parasite infection during pregnancy has been associated with iron deficiency, maternal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
(31 reference statements)
2
13
0
Order By: Relevance
“…Although seldom found, it has been reported in some studies in LMICs. For instance, Rodríguez-Morales et al [11] reported that the most important parasite representing a twofold risk for anemia at pregnancy was A lumbricoides, similar to Demeke G et al in Ethiopia [45].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although seldom found, it has been reported in some studies in LMICs. For instance, Rodríguez-Morales et al [11] reported that the most important parasite representing a twofold risk for anemia at pregnancy was A lumbricoides, similar to Demeke G et al in Ethiopia [45].…”
Section: Discussionmentioning
confidence: 62%
“…There are a few studies that link pregnant women with IPI to an increased risk of maternal complications and adverse perinatal outcomes such as anaemia, low birth weight, and perinatal mortality [11,[43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…In Sub-Saharan Africa, soil-transmitted helminths including hookworm, urogenital schistosomiasis, and other parasitic infections such as malaria contribute to the high anemia rates in women and young children [37]. Open Journal of Obstetrics and Gynecology Ferric Sodium EDTA is an iron chelate that has been used successfully as a dietary fortifier in several trials in the developing world [38] [39], as in this form, the iron is protected from inhibitors of iron absorption.…”
Section: Discussionmentioning
confidence: 99%
“…This risk increase even more during pregnancy due to polyuria, glycosuria, and pregnancy hormones. In almost 8 percent of all pregnant women, UTIs occur and 90 percent of the UTIs occur at 24 weeks of pregnancy 10 .…”
Section: Introductionmentioning
confidence: 99%